The Ideal Teacher Profile in the Perspective of Class VI Students in Madrasah Ibtidaiyah 12 Padang Sappa, Ponrang District, Luwu Regency - Umrah Umrah (P3I Luwu Raya, 2019)
This research is a qualitative descriptive field research that analyzes the data in depth based on the percentage of numbers. The results showed that: 1. The ideal teacher profile in the perspective of class VI Madrasah Ibtidaiyah 12 Padang Sappa, Ponrang District, Luwu Regency includes: a. Have an exemplary attitude in behavior, fear God Almighty, develop praiseworthy attitudes in everyday life, b. Interact and communicate well with school residents, c. Carry out guidance and counseling for students, d. Prepare learning administration, e. Mastering learning material, f. Maintain a harmonious relationship, h. Assess and praise the results in the teaching and learning process carried out by students. From the research and questionnaire results, it was found that: a. Teachers have exemplary attitudes in behavior, preach to God, and behave praiseworthy at MI 12 Padang Sappa received the most